2015
DOI: 10.1152/ajpgi.00278.2015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NHE8 expression impairs intestinal mucosal integrity

Abstract: The newest member of the Na(+)/H(+) exchanger (NHE) family, NHE8, is abundantly expressed at the apical membrane of the intestinal epithelia. We previously reported that mucin 2 expression was significantly decreased in the colon in NHE8(-/-) mice, suggesting that NHE8 is involved in intestinal mucosal protection. In this study, we further evaluated the role of NHE8 in intestinal epithelial protection after dextran sodium sulfate (DSS) challenge. Compared with wild-type mice, NHE8(-/-) mice have increased bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…SLC9A8 (solute carrier family 9 member A8) encodes a transmembrane protein that exchanges extracellular Na þ for intracellular H þ (37). It has been reported to be involved in intestinal mucosal integrity by regulating the functions of goblet and Paneth cells (38), and its loss has been shown to result in reduced mucin Mean normalized allelic fraction (mNAF) and mutation significance in the MiSeq data shown for the 71 genes selected for screening (Sets A, B, and C) in the extended set. Color indicates the mutation frequency of the gene, with darker shades corresponding to higher frequencies.…”
Section: Aasdhmentioning
confidence: 99%
“…SLC9A8 (solute carrier family 9 member A8) encodes a transmembrane protein that exchanges extracellular Na þ for intracellular H þ (37). It has been reported to be involved in intestinal mucosal integrity by regulating the functions of goblet and Paneth cells (38), and its loss has been shown to result in reduced mucin Mean normalized allelic fraction (mNAF) and mutation significance in the MiSeq data shown for the 71 genes selected for screening (Sets A, B, and C) in the extended set. Color indicates the mutation frequency of the gene, with darker shades corresponding to higher frequencies.…”
Section: Aasdhmentioning
confidence: 99%
“…NHE8 may compensate for the loss of NHE2 and NHE3 in knockout mice, suggesting the role of NHE8 in the intestinal sodium absorption in early life, when NHE2 ND NHE3 are at very low levels (316). Targeted ablation of the Slc9a8 gene in mice results in a higher incidence of gastric ulcer formation, impaired mucosal protection, and altered gut microbiota (177, 300, 315, 317, 321), pointing to the role of NHE8 in mucosal protection in the gut.…”
Section: Mammalian Monovalent Cation Proton Antiporter Superfamilymentioning
confidence: 99%
“…Goblet cells express NHE8, which is downregulated in rodent experimental colitis and in UC patients, and its deletion confers higher susceptibility with an enhanced T-helper 2–like response (174, 177, 311). Reduced expression or absence of NHE8 also leads to decreased Muc2 mRNA expression in goblets cells, and decreased mucosal expression of antimicrobial peptides (300). Reduced Muc2 expression is also detected in NHE8 −/− goblet cells and in intestinal organoids from Nhe8 -deficient mice (Xu et al, unpublished data).…”
Section: Na+/h+ Exchange In Pathological Statesmentioning
confidence: 99%
“…Moreover, its expression is not limited to the apical membrane; in vitro studies with ectopically expressed NHE8 have shown that it is both present and functional in the trans-Golgi network and multivesicular bodies 113 . It is broadly expressed in the colon, including the goblet cells, where it participates in the regulation of mucin 2 (Muc2) expression and mucous secretion 41, 114, 115. Although we observed a dramatic decrease in the expression of NHE8 in UC patients (Li et al, unpublished data), loss of NHE8 expression and activity may not contribute to inflammation-associated diarrhea directly because NHE8 -/- mice do not show symptoms of impaired Na + absorption or diarrhea 41 .…”
Section: Intestinal Na+/h+ Exchange In Clinical and Experimental Inflmentioning
confidence: 99%
“…Indeed, it is down-regulated and confers higher susceptibility during experimental colitis with a T-helper 2–like response 151, 152. Reduced expression or absence of NHE8 also is related to decreased Muc2 mRNA expression in goblets cells, and decreased mucosal expression of antimicrobial peptides 114 . NHE8 -/- mice have reduced Muc2 expression, which also could be reproduced in colonic organoids from this strain (Xu et al, unpublished data), and show a reduced inner mucous layer and closer proximity of luminal bacteria to the brush-border membrane 152 .…”
Section: Intestinal Na+/h+ Exchange In Clinical and Experimental Inflmentioning
confidence: 99%